Análise da oferta de vagas escolares no município de Taboão da Serra (SP) - Mitsuko Yamasaki Marques (Confins)
This article accounts for the methodology used to analyze the frequentation of the school facilities in Taboão da Serra (São Paulo), in order to measure the number of free places in the schools. The gathering of information is done in each school unit of the municipal network, in particular data on the distance between residence and school. The statistical processing was enriched by the possibilities of spatialization offered by the use of SIG software, in this case Maptitude. The results were consolidated in a document entitled Atlas for the Management of the School System, an invaluable help to define the Municipal Plan of Education and which was used as base with the decision-making on the improvement of the network schools.